The role of the professor researcher in Dentistry - Morales-Chávez, Mariana (2017)
Nowdays, academic instruction in any Dental school presents important challenges for both the university and professors. Due to the constant changes that the world faces; now more than ever the three pillars of university education: teaching, research and extension, must be fulfilled. The mere transmission of knowledge by the professor is no longer enough, equal importance has the student's exposure to social reality through extension, even more in scientific careers such as Dentistry. With that purpose, professors have the obligation to train the student as a researcher so that they are able to generate knowledge and provide answers to social problems. Hence, the professor must have certain features and develop a profile that allows him to transmit research skills. It is essential that the professor should be an example of intellectual production, as well as being up to date with the management of new technologies in scientific and social networks.